Corporate Social Responsibility Impact on Financial Performance - Dinda, Bahiira Albasitha Permata; Wicaksono, Septia; Hwihanus, Hwihanus (Asian Journal of Management Analytics, 2024)
The objective of this research is to explain Corporate Social Responsibility impact on financial performance in international companies. This research is a qualitative approach using secondary data obtained from research results, research reports, and scientific journals. The sampling method uses purposive sampling technique, using a sample of 5 research results. The results showed that Corporate Social Responsibility significantly contributes to the enhancement of a company’s financial success with multiple elements that play an important role in this relationship. Companies that are active in Corporate Social Responsibility tend to have better reporting, thus increasing transparency, reputation, and investment attractiveness that contribute positively to financial performance.